Volumetric modulated arc therapy: a dosimetric comparison with dynamic IMRT and step-and-shoot IMRT. Issue 4 (13th December 2020) - Raina, Payal; Singh, Sudha; Tudu, Rajanigandha; Singh, Rashmi; Kumar, Anup
Abstract: Aim: The aim of this study was to compare volumetric modulated arc therapy (VMAT) with dynamic intensity-modulated radiation therapy (dIMRT) and step-and-shoot IMRT (ssIMRT) for different treatment sites. Materials and methods: Twelve patients were selected for the planning comparison study. This included three head and neck, three brain, three rectal and three cervical cancer patients. Total dose of 50 Gy was given for all the plans. Plans were done for Elekta synergy with Monaco treatment planning system. All plans were generated with 6 MV photons beam. Plan evaluation was based on the ability to meet the dose volume histogram, dose homogeneity index, conformity index and radiation delivery time, and monitor unit needs to deliver the prescribed dose. Results: The VMAT and dIMRT plans achieved the better conformity (CI98% = 0·965 ± 0·023) and (CI98% = 0·939 ± 0·01), respectively, while ssIMRT plans were slightly inferior (CI98% = 0·901 ± 0·038). The inhomogeneity in the planning target volume (PTV) was highest with ssIMRT with HI equal to 0·097 ± 0·015 when compared to VMAT with HI equal to 0·092 ± 0·0369 and 0·095 ± 0·023 with dIMRT. The integral dose is found to be inferior with VMAT 105·31 ± 53·6 (Gy L) when compared with dIMRT 110·75 ± 52·9 (Gy L) and ssIMRT 115 38 ± 55·1(Gy L). All the techniques respected the planning objective for all organs at risk. The delivery time per fraction for VMAT was much lower than dIMRT and ssIMRT. Findings: Our results indicate that dIMRT and VMAT provide better sparing of normal tissue, homogeneity and conformity than ssIMRT with reduced treatment delivery time.